PERANCANGAN PROMOSI PESONA ALAM BUKIT LANGKISAU WEST SUMATERA MELALUI AUDIO VISUAL - RINDU WANDARA, Dr. Syafwandi, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Langkisau hill is one of the known tourist with beautiful objects and provide places that could spoil the eye, but many people might not know about the existence, activities and the beauty of the hills Langkisau. Video is a creatively processed documentation which is one of the modern communications media by showing the incorporation of moving images and sound, so that the target audience can find out more information disampaikan.Target audience obviously expected to be moreinterested to keep coming to visit tourist attractions in West Sumatra, especially in the South Coast namely Pesona Alam Bukit Langkisau with their video views as its main media and supported by various supporting media. Methods of data analysis in the design of this method 5W1H. W consists of What (what), Who (who), Where (where), When (when), Why (why), and How (how). Major media in this thesis is the audio-visual form of video. And media support in this thesis is a calendar, pin, leafleat, posters, T-shirts, stickers, keychains, and banners.Kayword: Video, Promotion, Langkisau Hill